2016
DOI: 10.12688/f1000research.9477.1
|View full text |Cite
|
Sign up to set email alerts
|

Muddled mechanisms: recent progress towards antimalarial target identification

Abstract: In the past decade, malaria rates have plummeted as a result of aggressive infection control measures and the adoption of artemisinin-based combination therapies (ACTs). However, a potential crisis looms ahead. Treatment failures to standard antimalarial regimens have been reported in Southeast Asia, and devastating consequences are expected if resistance spreads to the African continent. To prevent a potential public health emergency, the antimalarial arsenal must contain therapeutics with novel mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Drugs with improved efficacy and potency were introduced to deal with the resistance. Recent study on drug resistance showed that de novo resistances are appearing more rapidly [12,13]. The first case of drug resistance ever reported was in 1980, it was against Quinine [14].…”
Section: Treatment Regimesmentioning
confidence: 99%
“…Drugs with improved efficacy and potency were introduced to deal with the resistance. Recent study on drug resistance showed that de novo resistances are appearing more rapidly [12,13]. The first case of drug resistance ever reported was in 1980, it was against Quinine [14].…”
Section: Treatment Regimesmentioning
confidence: 99%
“…Namely, identifying the direct target(s) of an inhibitor provides the molecular basis for optimizing structure‐activity relationships and can also unveil novel druggable targets that in turn aid in target‐based drug discovery. Complicating drug‐target discovery efforts has been the increasing appreciation that many drugs, including antimalarial inhibitors, deliver their therapeutic effects by targeting multiple proteins [9–11] . This suggests that comprehensive profiling of drug targets is necessary to elucidate complicated mechanisms of drug action and prioritize compounds for further drug development.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, antimalarial drugs have been instrumental in preventing the most aggressive and lethal forms of the disease caused by Plasmodium falciparum . However, due to the limited structural diversity within the chemical scaffolds of current clinically-available drugs and the increased incidence of drug resistance, new antimalarial compounds with novel modes of action must be identified 2 4 .…”
Section: Introductionmentioning
confidence: 99%